Relação entre a qualidade hídrica superficial e a dinâmica da paisagem em quatro sub-bacias hidrográficas com alta densidade demográfica na região sudeste do Brasil - Dorici, Mariana (2021)
The deterioration of water bodies has become an increasingly worrying problem as human activities cause significant changes in the physicochemical properties of water and a series of environmental and human health problems. However, the protection of water quality is still a challenging task for humanity, because the integrity of water resources is associated, in a complex way, with a series of natural and anthropogenic factors and the interactions between them. In this sense, several studies have been carried out in recent years, showing evidence that the landscape structure has a significant relationship with the water quality of surface water bodies. Therefore, understanding the interaction between the landscape structure of a watershed and the water quality of its surface water resources is of paramount importance for watershed management. Thus, this research aimed to analyze the relationship between the dynamics of land use and land cover and landscape metrics with the physical, chemical and microbiological parameters of water, in four hydrographic sub-basins, located in the Water Resources Management Unit of the Piracicaba, Capivari and Jundiaí Rivers (PCJ). Initially, the physical, chemical and microbiological parameters of surface water were analyzed, identifying the variations that occurred in the selected period (2011-2014-2017), this analysis showed that the water quality of the study area underwent significant variations in 2014 and that its deterioration was related to rainfall data. Then, an analysis of the dynamics of land use and land cover and an analysis of the landscape pattern was carried out, pointing out the importance of a joint analysis between these two factors to understand the structure of the landscape and its relationships with other environmental factors, such as, example, water quality. Finally, a statistical analysis was carried out to investigate the relationship between the structure of the landscape and the parameters of water quality, using the redundancy analysis (RDA). The RDA is used to analyze the main causes of data variation, exposing the correlation between the response and its explanatory variables. Based on their results, it was concluded that the land use and land cover class "urbanized areas" was the most relevant and explanatory for the degradation of surface water quality in the study area and the classes "natural vegetation areas" and "continental waters ” were the most related to the pH and nitrate nitrogen parameters. To understand this relationship, the analysis of the landscape configuration and seasonal variations became essential. Thus, it was identified that the IJI, CONTAG and LPI metrics were essential to understand the responses found. These responses showed deficiencies in the management of hydrographic basins and that a series of actions need to be implemented so that decision makers enforce environmental legislation, maintaining the preservation of large forest remnants and the conservation of permanent preservation areas. Emphasizing the need for integrated and continuous analysis and management of water resources, so that planning and responses to critical and adverse situations can be adequate and efficient.